PENGARUH DISIPLIN, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KABUPATEN BOYOLALI - Dewi, Rizki Rahma; Purwanto, Hari; Rahayu, Listyowati Puji (Universitas Boyolali, 2023)
The ability of human resources is one of the important assets to achieve the vision, mission and goals of an agency. Discipline, motivation, and work environment are factors that influence an employee’s performance. The purpose of this study is to determine the effect of discipline, motivation, and work environment on the performance of BPBD Boyolali Regency employees. This study uses a quantitative research type with a questionnaire as a data collection tool. The population in this study were employees of the Boyolali Regency BPBD office with a total of 54 employees as respondents. Data testing techniques in this study were validity and reability test, classic assumption test, t test, f test, coefficient of determination test, and multiple linear regression analysis test.The result of this studi indicate that the work discipline variable partially does not have a significant effect on employee performance with a significance value of 0,192 > 0,05. Partially work motivation variable has no significant effect on employee performance with a significance value of 0,143 > 0,05. Work environment variable partially have a significant influence on employee performance with a significance value of 0,000 > 0,05. The variables of work discipline, work motivation, and work environment simultaneously affect employee performance with a significance value of 0,000 < 0,005. And the result of the determination test show that the effect of work discipline, work motivation, and work environment on the performance of employees at the BPBD Boyolali Regency office is 78,7 %.